2005
DOI: 10.1111/j.1745-7254.2005.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine protected photoreceptor cells of rats by modulating nuclear translocation of NF-kappaB1

Abstract: Aim: To evaluate the effect of tetramethylpyrazine (TMP) injection on retinal damage induced by N-methyl-N-nitrosourea (MNU) in rats and on nuclear factorkappa B (NF-κB) family members. Methods: Female Sprague-Dawley (SD) rats were randomly divided into groups: (i), control group; (ii), model group; and (iii), TMP-injection groups, in which the rats were subdivided into 40 mg/kg, 80 mg/kg and 160 mg/kg groups. Drugs were injected ip into 47-day-old SD rats once a day. At 50 days of age, all rats in the model g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Accumulating evidence suggests that the cytoprotective effect of TMP might be mediated by its antioxidant potentialities in cells (Shih et al, 2002;Zhang et al, 2003;Yang et al, 2005). In agreement with these observations, we detected a strong protective effect of TMP on retinal cells against ROS generator, H 2 O 2 , -induced cytotoxicity.…”
Section: Tmp Attenuated Hydrogen Peroxide-induced Cell Death In Retinsupporting
confidence: 80%
See 1 more Smart Citation
“…Accumulating evidence suggests that the cytoprotective effect of TMP might be mediated by its antioxidant potentialities in cells (Shih et al, 2002;Zhang et al, 2003;Yang et al, 2005). In agreement with these observations, we detected a strong protective effect of TMP on retinal cells against ROS generator, H 2 O 2 , -induced cytotoxicity.…”
Section: Tmp Attenuated Hydrogen Peroxide-induced Cell Death In Retinsupporting
confidence: 80%
“…Improvements of learning and cognitive function by TMP were also reported in rodents following D-galactose-or arterial occlusion-induced brain lesions (Ni et al, 1995;Zhang et al, 2004). In addition, TMP protects photoreceptor from drug-induced damage as well as optic nerve axon lesions caused by intraocular hypertension (Li et al, 2000;Yang et al, 2005). Despite accumulating reports showing the cytoprotective effects of TMP, the pharmacological mechanism of TMP for neuroprotection is still poorly understood at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Accumulating evidence suggests that TMP may have therapeutic potential as a complementary therapy for various ocular diseases, including vascular retinopathy, corneal neovascularization, optic neuropathy, and glaucoma. 16,[21][22][23] In particular, our latest investigation implicated TMP in attenuation of TGF-b-induced pathologic changes in trabecular meshwork cells, showing that it inhibits cytoskeleton remodeling and ECM accumulation through the SDF/CXCR4 axis. 24 Prompted by these previous reports, we sought to characterize the bioactivity of TMP and its underlying mechanism.…”
mentioning
confidence: 99%
“…Recently, the pharmacological effects of TMP have been expanded from its well-known vasodilatory actions and antiplatelet activity to a wide variety of activities such as anti-inflammatory, anti-stress [tetramethylpyrazine protects against palmitate-induced oxidative damage and mitochondrial dysfunction in C2C12 myotubes (16)], and antiapoptosis activity. TMP can protect against MNU-induced retinal damage (17), iron-induced oxidative damage and apoptosis in cerebellar granule cells (18), gastric mucosal injury in a rat model of acute necrotizing pancreatitis, spinal cord ischemia, gentamicin-induced apoptosis in murine renal tubular cells (19), rat asthma, acute liver and lung injury after burn trauma (20), acute myocardium injury after thermal trauma (21) and accelerated anti-glomerular basement membrane antibody nephritis (22). Several studies have also reported that one of the underlying mechanisms of TMP is its reactive oxygen species (ROS)-scavenging activity (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%